Answer:
9,18, and 36
Step-by-step explanation:
9*4=36 and 9*1=9
18*2=36 and 9*2=18
36*1=36 and 9*4=36
The correct answer is
![A) x^2 - 6x + 9](https://tex.z-dn.net/?f=A%29%20x%5E2%20-%206x%20%2B%209)
In fact, this is a trinomial of the form
![ax^2-bx+c](https://tex.z-dn.net/?f=ax%5E2-bx%2Bc)
, whose solutions are given by
![x_{1,2}= \frac{-b\pm \sqrt{b^2 -4ac} }{2a}](https://tex.z-dn.net/?f=x_%7B1%2C2%7D%3D%20%20%5Cfrac%7B-b%5Cpm%20%5Csqrt%7Bb%5E2%20-4ac%7D%20%7D%7B2a%7D)
Using this formula for the trinomial of the problem, we find:
![x1,2= \frac{6 \pm \sqrt{6^2-4\cdot 1\cdot 9}}{2} =3](https://tex.z-dn.net/?f=x1%2C2%3D%20%20%5Cfrac%7B6%20%5Cpm%20%5Csqrt%7B6%5E2-4%5Ccdot%201%5Ccdot%209%7D%7D%7B2%7D%20%3D3)
<span>we see that this trinomial has two coincident solutions (x=3 with multiplicity 2). This means that it can be rewritten as a perfect square, in the following form:
</span>
![(x-3)^2](https://tex.z-dn.net/?f=%28x-3%29%5E2)
<span>
</span>
Answer:
347,168 rounded to the nearest ten thousands would be 350,000.
Step-by-step explanation:
When rounding to the nearest ten thousands, you rely on the thousands place value to indicate whether to round up or down. 5 or higher give it a shove, 4 or less let it rest. 7 is in the thousands place meaning we round up. 4 is in the ten thousands place meaning it becomes 5. 347,168 rounded to the nearest ten thousands would be 350,000.
Answer:
It is the second triangle.
Step-by-step explanation:
This is because the area of the square is given as 25^2 as the perpendicular, 144^2 as the base, and the hypotenuse is 169^2.
Length of the perpendicular = 5^2 (Because 25^2 / 5^2)
Length of the base = 12^2
Length of the hypotenuse = 13^2
So, the Pythagoras theorem is,
=> ![H^{2} = P^{2} + B^{2}](https://tex.z-dn.net/?f=H%5E%7B2%7D%20%3D%20P%5E%7B2%7D%20%2B%20B%5E%7B2%7D)
=> ![13^{2} =12^{2} +5^{2}](https://tex.z-dn.net/?f=13%5E%7B2%7D%20%3D12%5E%7B2%7D%20%2B5%5E%7B2%7D)
This is true, because, 13*13 = 12*12 + 5*5
=> 169 = 144 + 25
=> 169 = 169
If my answer helped, kindly mark me as the brainliest!!
Thanks!!
Answer:
m∠TUV = 105
Step-by-step explanation:
From the question given above, the following data were obtained:
m∠TUN = 1 + 38x
m∠NUV = 66°
m∠TUV = 105x
m∠TUV =?
Next, we shall determine the value of x. This can be obtained as illustrated below:
m∠TUV = m∠TUN + m∠NUV
105x = (1 + 38x) + 66
105x = 1 + 38x + 66
Collect like terms
105x – 38x = 1 + 66
67x = 67
Divide both side by 67
x = 67 / 67
x = 1
Finally, we shall determine the value of m∠TUV. This can be obtained as shown below:
m∠TUV = 105x
x = 1
m∠TUV = 105(1)
m∠TUV = 105